Reducing the Damage: Dilemmas of Anti-Trafficking Efforts among Nigerian Prostitutes in Palermo - Cole, Jeffrey (Anthropologica, 2022)
Over the past 10 years, trafficked Nigerian women have become synonymous with street prostitution in Palermo, Italy. In this article, I attempt to assess a project that offers medical care, free condoms, advice on safe practices and other forms of assistance to Nigerian prostitutes. This assessment reveals the strengths and weaknesses of Italy's innovative anti-trafficking initiatives. The program reduces many of the dangers involved in street prostitution, but debt bondage to traffickers, family obligations and threats of supernatural retribution stymie efforts to separate women from their exploiters and render prosecution of criminals difficult. Those who do complete the rehabilitation program face a difficult integration into Italian society.